Phylogenetics and diversification history of African rattans (Calamoideae, Ancistrophyllinae) - (:unkn) unknown (My University, 2016)
Even though African rain forests display high levels of local species diversity and endemism, their lower continental species diversity when compared with the Neotropics and Asia is paradoxical. This disparity is mainly thought to be linked to either important extinction events during the Pleistocene or at the Eocene–Oligocene boundary. African rattans or climbing palms are one of the most diverse clades of palms in Africa, representing one-third of all known species. Here, we reconstruct the phylogeny and temporal evolution of African rattans (Arecaceae: Calamoideae: Lepidocaryeae: Ancistrophyllinae) to test the two main hypotheses of palm evolution in Africa. We constructed a near-complete, dated species-level phylogenetic tree for subtribe Ancistrophyllinae using plastid and nuclear markers. The generic relationships between Ancistrophyllinae were fully resolved and species-level relationships are well to weakly supported. Ancistrophyllinae diversified during the Eocene with most species originating during the late Miocene after 10 Mya. This result is in agreement with several other studies suggesting a pre–Pleistocene origin of the extant African flora. Ancistrophyllinae display an anti-sigmoidal lineage-through-time plot with a moderate overall extinction fraction. Our simulations suggest important roles for an ancient extinction event at the Oligocene–Eocene boundary. In contrast, the hypothesis of an important extinction event in palms during the late Pliocene at 3 Mya is not supported. We suggest that the evolutionary history of African rattans has undergone a constant diversification rate punctuated by one or several important extinction events during the first part of the Cenozoic with most species diversity accumulating during the late Miocene and Pliocene.
Keywords: African Research